The Geopolitical Thought of Józef Piłsudski and his Political Camp Concerning Central Europe in Comparison to the Achievements of Other Political Centers - Jakub H. Szlachetko (Journal on European History of Law)
The paper focused mainly on the ideas created by Marshall himself or people from his closest circle. It is worth stressing that federalism, the policy of balance of power or colonialism are not the only manifestations of spatial thinking in Piłsudski’s camp’s foreign policy. During the interwar period, the members of various social organizations united in the so–called Zet Movement were very active, and created interesting variants of the ideas outlined in the article. During the Second World War and the People’s Republic of Poland, owing to political reasons, Piłsudski’s camp’s thought on Central Europe did not influence the reality of the time at all. Yet it persisted within certain circles of the anti–communist independence movement until the 21st century, and it is at present, to a smaller or greater extent, implemented by the right–wing political parties.